An analytical model for the monitoring of pore water pressure inside embankment dams. (1st April 2018) - Guo, X.; Baroth, J.; Dias, D.; Simon, A.
Highlights: An analytical model is introduced for the monitoring of pore water pressure inside embankment dams. The model allows taking into account the delayed hydrostatic effect and eables an earlier detection of abnormal pore water pressures. An application of the model to a French earth dam is provided. Abstract: The hydraulic behaviour of embankment dams is influenced by many factors, such as hydrostatic loads and settlement. Particularly, the delayed response due to the diffusion phenomena plays a crucial role in the interpretation of the monitoring data gathered in embankment dams. The paper describes a statistical analysis model named EFR (EFfet Retard - Delayed effect), based on the HST (Hydrostatic-Season-Time) model, for the monitoring of pore water pressure inside embankment dams. The model allows separating the influence of the most important factors and takes into account the delayed hydrostatic effect. The use of this model leads to a better estimation of the irreversible trend and enables an earlier detection of abnormal pore water pressures. An application of this model to a French embankment dam is provided in the second part of the paper. Based on this application, the influence of different diffusion models, calculation methods for the equivalent reservoir water levels and the irreversible term versions on the EFR analysis results are discussed.